Modeling speeds of weaving sections at U-turn slots in Metro Manila - Galiza, Ronald John S (2006)
The closure of signalized intersections and the rerouting of traffic into midlock U-turn median openings (U-turn slots) paved the way for free-flow traffic conditions (uninterrupted flow) in an intersection. However, direct left turn (DLT) vehicles will now have to take a series of right-turn plus U-turn (RTUT) maneuvers in order to duplicate the same path taken prior to the closure. As a consequence, RTUT vehicles must weave across (lane change) into the innermost lane towards the U-turn slot. Currently, methods for analyzing the speeds in the weaving were derived exclusively on freeway weaving sections. Thus, there is a need to develop a method to estimate these speeds specifically for urban streets.